THU0111 Novel autoantibody profiles in rheumatoid arthritis and their association with radiographic progression in the scottish early rheumatoid arthritis inception cohort and biobank (SERA). (15th June 2017) - Nijjar, J; Morton, F; Gilmour, A; Paterson, C; Bang, H; Heijde, D van der; Raza, K; Buckley, C; Porter, D; McInnes, I
Abstract : Background: Antibodies against citrullinated peptides are useful in the diagnosis of rheumatoid arthritis (RA) and are associated with poorer prognosis and greater radiographic progression. Novel autoantibodies recognising several post-translational modifications (PTM) are now emerging including anti-carbamyl, and anti-acetyl antibody classes. Less is known of their prognostic significance. Objectives: To determine the prevalence of autoantibodies to modified vimentin and/or CCP2 (anti citrullinated (CCP), anti carbamylated (Carb), anti acetylated (Acet)) in a subset of the Scottish Early RA (SERA) inception cohort (n=212) and to correlate them with baseline and radiographic progression over 12 months. Methods: Baseline and 12m hand and foot radiographs were scored by two readers independently, blinded to patient information and time order according to the Sharp van der Heijde score (SvH). Serum samples from the SERA biobank were analysed with recently published anti-modified protein assays. Patients with citrullinated antibodies (CCP) had antibodies to modified vimentin and/or antibodies to CCP2. Clinical, radiographic and autoantibody data were analysed in R. Results: See Table 1 . In patients with early RA four main antibody profiles were detected: patients with anti CCP antibodies (n=65), antibodies to anti CCP and anti Carb (n=36), antibodies to all three PTM (n=76) and antibody negative patients (n=35). Overall there was low radiographic progression in this sample of the SERA cohort. EULAR non-responders had greater progression compared to good responders (Least square mean difference in SvH over 12 m of 1.6, p=0.019). Baseline SvH erosion scores are 4.4 points higher in the CCP_Carb group compared to CCP alone (p=0.009) (Table 2 + Fig 1). Total SvH 12m progression is 1.3 points higher in the triple positive group compared to the CCP group alone (p=0.016) (Table 2 + Fig 2). Total SvH progression is also higher when comparing the triple positive to the negative group (p=0.046). Conclusions: RA patients with antibodies to citrullinated peptides only have lower baseline erosions and less radiographic progression over 12m compared to those with a wider autoantibody repertoire. Baseline differences in erosion suggest that these antibodies may be pathogenic during the pre-RA disease process. Radiographic progression increases with autoantibody repertoire suggesting ongoing immune activation. Disclosure of Interest: J. Nijjar: None declared, F. Morton: None declared, A. Gilmour: None declared, C. Paterson: None declared, H. Bang Employee of: Orgentec Diagnostike GmbH and holds patent for mutated citrullinated vimentin as diagnostic tool, D. van der Heijde Employee of: Director of Imaging Rheumatology, K. Raza: None declared, C. Buckley: None declared, D. Porter Grant/research support from: Pfizer co-funded the SERA cohort, I. McInnes: None declared